DDDR-10. INHIBITING INSULIN SIGNALING REVERSES RESISTANCE TO PI3K-MTOR INHIBITORS IN AGGRESSIVE PEDIATRIC HIGH-GRADE GLIOMAS. (14th November 2022) - Gatesman, Taylor; Halligan, Katharine; Halbert, Matthew; Stanton, Ann-Catherine; Cruz, Andrea; Golbourn, Brian; Pollack, Ian F; Mack, Stephen C; Agnihotri, Sameer
Abstract: Primary central nervous system (CNS) tumors are now the most common cause of childhood cancer–related deaths. Pediatric high-grade gliomas (pHGGs) are among the most lethal brain tumors with a 5-year survival rate of only 20%. MYCN pHGGs represent one subgroup with an unmet need for therapeutics. MYCN belongs to the family of MYC transcription factors that regulate numerous cancer hallmarks such as proliferation, apoptosis, and metabolism. While no direct inhibitors of MYCN are in clinical trial, current strategies focus on targeting the MYCN mediated transcriptional machinery or cell cycle regulators. Lack of relevant pHGG models for pre-clinical testing contribute to limited therapeutic efficacy. To address these knowledge gaps, we developed a novel mouse model of MYCN pHGG using the FLEx-Cre switch system, whereby neural stem cells are selectively delivered with MYCN cDNA and shRNA targeting the tumor suppressor genes p53 and Pten and form tumors in vivo . We identified that this model harbors hyper-activation of the PI3K/AKT/mTOR signaling pathway. We demonstrate that dual PI3K-mTOR blood brain barrier penetrant inhibitors are effective in reducing pHGG growth and MYCN protein levels. Because treatment-resistance is a fundamental feature of pHGGs, we developed a novel drug-resistance model of MYCN pHGG as a mechanistic tool to identify relevant resistance mechanisms. Using transcriptome analysis, we identified the insulin growth factor signaling pathway as our top mechanism of resistance. We hypothesized that MYCN is a critical driver of pHGG and can be effectively targeted via dual inhibition of PI3K-mTOR and IGF/Insulin signaling pathways. We tested next generation inhibitors of IGF and PI3K/mTOR pathways and performed genetic and pharmacological assays in our MYCN pHGG and human MYCN pHGG cells. Inhibition of both pathways in our MYCN pHGG model and human MYCN cells were synergistic, leading to significant decreases in cell growth and MYCN signaling.